(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Antenatal care knowledge proves to be vital in accessing antenatal care and improves in the health care seeking behaviour of antenatal women. Aim: To assess the knowledge regarding antenatal investigation among primigravida. Setting & Design: Study was done in antenatal clinics of selected hospital & the design adopted for this study was Non experimental descriptive design. Materials & Methods: A total of 100 participants were selected for the study using a non probability purposive sampling method. A set of questionnaire which was based on knowledge regarding antenatal investigations was constructed and reliability score achieved was 0.8 Results: Results revealed that 49% samples had average knowledge regarding antenatal investigation, 47% had poor knowledge, whereas only 4% had good knowledge. The means score was 7.99 with SD +2.54.Conclusion: There is a statistically significant relationship between Primigravida mother’s age and the number of prenatal appointments, which reveals that more the number of visits the more exposure to knowledge could be conclusive.